Co-location of eruption sites of the Siberian Traps and North Atlantic Igneous Province: Implications for the nature of hotspots and mantle plumes - Smirnov, Aleksey V.; Tarduno, John A. (Earth and Planetary Science Letters, 2010)
One of the striking exceptions to the mantle plume head-tail hypothesis that seeks to explain magmatism of large igneous provinces (LIPs) and hotspot tracks is the ~250. million-year-old Siberian Traps. The lack of a clear hotspot track linked to this LIP has been one motivation to explore non-plume alternative mechanisms. Here, we use a paleomagnetic Euler pole analysis to constrain the location of the Siberian Traps at the time of their eruption. The reconstructed position coincides with the mantle region that also saw eruption of the ~. 61-58. million year-old North Atlantic Igneous Province (NAIP). Together with LIP volume estimates, this reconstruction poses a dilemma for some non-plume models: the partial-melts needed to account for the Siberian Traps should have depleted the enriched upper mantle source that is in turn crucial for the later formation of the NAIP. The observations instead suggest the existence of a long-lived (> 250. million-year-long) lower mantle chemical and/or thermal anomaly, and significant temporal changes in mantle plume flux. Â© 2010 Elsevier B.V.